Halogens effect on spectroscopy, anticancer and molecular docking studies for platinum complexes - Khalid, Hunar Hama; Erkan, Sultan; Bulut, Niyazi (Elsevier Gmbh, 2021)
Pt(dpb)Cl, Pt(Fdpb)Cl, Pt(F2dpb)Cl and Pt(dpb)I complexes are examined by computational chemistry method in all aspects. Hartree-Fock (HF) and Density Functional Theory (DFT) methods at B3LYP and M062X level of functions with CEP-4G, CEP-31G, CEP-12G, LANL2DZ, LANL2MB, and SDD basis sets are used in calculation to obtain an optimal level. Spectral analysis (1H-NMR, 13C-NMR, IR and Emission) calculations are reported and compared with the available experimentally data. To discuss activities of the systems at a molecular level, pharmaceutically active four platinum complexes were studied. In addition, biological activity studies of the complexes have been done by using a molecular docking support and finally emission spectra and OLED properties of platinum complexes were examined. For the first time it was found that platinum complexes may have some photoactive chemotherapeutic properties and can be considered as an anticancer drugs.
Keywords: Platinum complexes; FTIR; NMR; Molecular docking; Anti-cancer